2006
DOI: 10.1007/s10495-006-8761-4
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol treatment induces testicular oxidative stress and germ cell apoptosis in rats

Abstract: In order to understand the pathogenesis of estradiol induced effects in the seminiferous epithelium, studies were undertaken in adult rats with estradiol-3-benzoate administered for different durations. After 30 d of treatment, a significant rise in lipid peroxidation with concomitant fall in the activities of superoxide dismutase and catalase was observed. Both, serum and intra-testicular testosterone levels were found severely depleted. Seminiferous epithelium was devoid of elongated spermatids and spermatoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 47 publications
(46 reference statements)
2
43
0
Order By: Relevance
“…Such alteration in the hormonal milieu induces hypospermatogenesis leading to reduced testicular weight in rodents. Chronic estrogen treatment results similar alterations in reproductive hormone levels that impairs spermatogenesis [32]. In the present study too, spermatogenesis is not completely arrested but impaired with significant reduction in the number of immature germ cells/tubule (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Such alteration in the hormonal milieu induces hypospermatogenesis leading to reduced testicular weight in rodents. Chronic estrogen treatment results similar alterations in reproductive hormone levels that impairs spermatogenesis [32]. In the present study too, spermatogenesis is not completely arrested but impaired with significant reduction in the number of immature germ cells/tubule (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…For example, Maheshwari et al (2009) demonstrated that H 2 O 2 -elicited apoptosis of testicular germ cells is associated with activation of the p53, Bax, Fas/Fasl, and a simultaneous decrease in the Bcl-2 expression. It was also observed by Chaki et al (2006) that an elevated expression of cell death effector Bax may contribute to the rat germ cell apoptosis with estradiol-3-benzoate administered.…”
Section: Discussionmentioning
confidence: 96%
“…Rats treated with ammonium molybdate exhibited an increase in lipid peroxidation in the testis which could be due to concomitant increase in the generation of free radicals or reduced content/activity of antioxidants in testis. Reduced level of intratesticular testosterone might also be responsible for suppressed expression of antioxidant enzyme with a concomitant increase in peroxidative damage, disruption of spermatogenesis and an increase in germ cell apoptosis (Peltola et al, 1996;Chaki et al, 2006).…”
Section: Discussionmentioning
confidence: 99%